PENGEMBANGAN BUKU DIGITAL BERBASIS STEM MATERI PENCEMARAN TANAH KELAS VII SMPN 2 RAMBIPUJI - Zaenab Nur Hafila; Haning Hasbiyati; Siti Roudlotul Hikamah (Bio-Lectura : Jurnal Pendidikan Biologi, 2023)
The purpose of the research is the development of STEM-based digital book media products in science subjects, especially soil pollution material that can be used and feasible as student learning media. The type of research is R&D (Research and Development) development using the 1999 Plomp model. Plomp’s design has three stages, namely from analysis, design and development, and evaluation. The trial on the digital book consisted of validity tests on material and media validators. Data analysis obtained from the validity test results from material experts showed that the book was very effective with an average score of 90%, while the validity test results from media experts showed that STEM-based digital books entered the effective criteria with an average score of 81,66%. Based on the results of the validity test above, the STEM-based digital book on soil pollution material is declared feasible to use.